Analisis Kepuasan Konsumen pada Produk Waralaba Teh cap Poci di Kecamatan Denpasar Selatan Kota Denpasar - LALALA, EDEN POSTER; SUAMBA, I KETUT; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017), 2017)
Analysis of Customer Satisfaction on Franchise Products of Cap Poci Teain the Sub-District of Southern Denpasar of Denpasar City Competition is common and cannot be avoided, not least in the franchise tea of cappoci. Employers of franchise tea of cap poci must continue to innovate or to improvethe shortcomings so that consumers do not run into other products. Consumerbehavior may help explain how consumers obtain satisfaction. This study aimed todetermine the level of customer satisfaction on the franchise tea of cap poci and whatactions should be conducted based on matrix of Importance-Performance. Thelocation of research was in South Denpasar Sub-District as having the greatestpotential consumers. The total sample of 30 respondents and sampling wasconducted by accidental sampling. The data collection includes quantitative data andqualitative data derived from primary and secondary data. Data collection methodsused were interviews and literature studies. Methods of data analysis usingdescriptive analysis, Importance-Performance Analysis and Custumer satisficationIndex. Based on the research results, the value or rate of CSI calculation was69.34%. The CSI Value of the franchise iced tea products of tea cap poci meets thecriteria of satisfied. But still need increased performance. Based on the Importance-Performance Matrix, the product attributes that need to be improved are: hygiene,price, and taste attributes.
Keywords: customer; satisfaction; franchise; importance-performance analysis